Root damage induced by intraosseous anesthesia–An in vitro investigation - Graetz, Christian (Medicina Oral S.L., 2013)
Objectives: The principle of the intraosseous anesthesia (IOA) relies on the perforation of the cortical plate of the bone for direct application of the local anesthetic solution into the underlying cancellous structures. During this procedure, IOA needles might accidentally come in contact with the tooth roots. The aim of the current in vitro study was to examine the consequences of this ‘worst case scenario’ comparing five commercially available IOA systems. Material and Methods: Extracted human roots were randomly perforated using five different IOA systems with a drilling time ≤5s. To simulate normal in vivo conditions, the roots were kept humid during the drilling procedure. Data was statistically evaluated using F-test (SPSS16, SPSS Inc., Chicago, USA) and the significance level was set at p≤0.05. Results: All examined systems resulted in root perforation. Drill fractures occurred in either none 0% (Quicksleeper®, Anesto®, Intraflow®, Stabident®) or 100% (X-Tip®) of the applications. Excessive heat generation, as evident by combustion odor as well as metal and tooth discoloration, appeared in 30% (Quicksleeper®), 40% (Anesto®), 60% (Intraflow®), 90% (Stabident®) and 100% (X-Tip®) of all perforations. Conclusion: Within the limits of in-vitro studies, the results show a potential for irreversible root damage that might be inflicted by an improper use of IOA systems. Key words:Intraosseous anesthesia, complication, root damage.